Optimal concentration of Syzygium aromaticum powder added to Anchovy TURLM Medium to Prevent The Degradation Shape of Mycobacterium tuberculosis Cells - Rohmi Rohmi; Maruni Wiwin Diarti; Ayu Anulus; Yunan Jiwintarum (poltekkes kemenkes mataram, 2022)
Alternative clinical diagnostic media for Mycobacterium tuberculosis (MTB) include Anchovy Sweet Seaweed Medium (TURLM). This media reported has good sensitivity and specificity, as well as growth speed, colony count, and fertility rates for MTB examination. In this study, six different types of clove flower powder were added to the TURLM media (Syzygium aromaticum). The goal of this study was to look at the vegetative shape of MTB bacteria in six different TURLM variations. This study was conducted at Microbiology Laboratory of the Medical Laboratory Technician Department at Politeknik Kesehatan Kementerian Kesehatan in Mataram, Indonesia. These findings revealed that complete MTB vegetative cells were mostly found in TURLM media with the addition of 0.5 g clove flower powder